Assembled sections of two blocks stacked on the jagati - Temples of India Project Team (Jio Institute, 2024)
Debris from the original temple was salvaged when the current temple was reconstructed in the 1940s. These have been assembled in parts to form the jagati (raised platform). However, it is not known where they were located in the original temple or if they came from multiple structures. The assembled sections here consist of two blocks stacked on the jagati. The upper block has the kalpavrisksha (tree of life) motif running along a central band. The panels on either side are damaged but visible features include the kalpa lata (creeper) motif (bottom left), the purna ghata (overflowing pot of prosperity) motif (mid-sections), and the kirtimukha motif (bottom right). The block in the middle has the ardha padma (half lotus) motif.